Analisis Validitas E-LKPD Interdisipliner Berbasis Projek Penguatan Profil Pelajar Pancasila Tema Kewirausahaan - Fatni Mufit; Hayyu Yumna; Aisyah Rehan Fadhillah; Desnita (JURNAL FIRNAS, 2025)
Strengthening the Pancasila Student Profile (P5) is an essential aspect of implementing the Merdeka Curriculum, aiming to build student character through project-based learning. This study aims to develop and validate a P5-based E-Worksheet (E-LKPD) titled "Penenrapan Teknologi dalam Pengolahan Kolang-Kaling Menjadi Aneka Selai Berbasis Konsep Zero Waste". The research employed a Research and Development (R&D) method using the ADDIE development model. Validation was conducted by three experts using a Likert-scale instrument and analyzed with Aiken's V formula. This article presents the validation results by instructional design experts. The validation covered several aspects, including content feasibility, presentation, language, visual appearance, the dimensions of the Pancasila Student Profile, and the entrepreneurship theme. The results showed high validity indices ranging from 0.89 to 0.98, categorized as valid. The average validity score of the E-LKPD was 0.95, indicating that the developed E-LKPD is suitable for practical implementation by both teachers and senior high school students.